The role performed by the teacher’s question in the learning of quadratic function in an exploratory mathematics class - Silva, Anaís Veloso; Viseu, Floriano; Menezes, Luís (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Communication plays a key role in teaching and learning processes. Questions are a communicational act greatly used by teachers to structure their discourse, establish dynamics, and foster interaction between the different participants in the classroom. In view of these potentialities of questions in the classroom context, we have developed a teaching experiment with the aim of understand the role of the teacher's question in the learning of topics on functions. Considering the nature of this aim, a methodology of qualitative and interpretative nature was used. The data collection was based on the students’ written productions and on the audio and video recordings of a mathematics class of a Grade 10 educational group (in northern Portugal). Data analysis is based on content analysis techniques, crossing collected data and categories emerging from the literature. The study revealed that the teacher’s questions alternated between confirmation, focalization, and inquiry, with inquiry prevailing. Questions aimed at testing the student’s knowledge gave both the teacher and actual student important information. Questions that focused the student’s attention on a particular detail enabled the students to organize their reasoning and structure their answer. Questions that required the students to explain or justify their thoughts were those that proved to most contribute to the development of the student’s reasoning process.